Evaluating the effect of the COVID-19 pandemic on the use and impact of social media in the urology residency match: A review of the literature - Yelton, Brent; Patel, Shivam; Shanholtzer, Andrew; Walter, Brianna; Jafri, Syed Mohammad (Frontiers in Urology, 2022)
Social media (SoMe) use within healthcare has changed significantly since the start of the COVID-19 pandemic. This project highlights recent changes in SoMe use within the field of urology and summarizes how they have impacted the urology residency application and match process. A literature review of the PubMed, Embase, Cochrane, Scopus, PsycINFO, and Web of Science databases was performed on March 19th, 2022 for relevant studies regarding the use of SoMe in the American urology residency application and match process. Articles not published in English, published prior to 2019, or focusing on residency matches outside of the United States were excluded. The initial search yielded 202 unique results, of which, after independent review, a total of nine texts were deemed appropriate for analysis. Of the nine sources, six were peer-reviewed articles, two were published conference abstracts which included data, and one was a research letter. These studies consistently found that both urology applicants and residency programs increased their SoMe use following the start of the COVID-19 pandemic as the percentage of programs (26-50% to 51-75%) and percentage of applicants (44% to 80%) participating in SoMe for professional purposes increased from 2018-2019 to 2021. Notably, Twitter was the most popular SoMe platform used. Among urology applicants, 43-61% found SoMe to have the greatest utility in providing information about specific programs. There was also consistency between studies in finding that SoMe use played a minimal role in whether or not a student matched, as only 3-6% of program directors reviewed applicants' SoMe during the application and match process, while as many as 80% reported that SoMe had no role in the assessment of applicants. With programs continuing to see SoMe as a method of reaching out to applicants, increases in usage will likely continue even after the COVID-19 pandemic ends. In turn, it will become increasingly important for students to be mindful of how and what they post on SoMe. Continuing to analyze and reevaluate the benefits and drawbacks of these SoMe tools will remain important as virtual interactions become increasingly relevant to the field of urology.